2003
DOI: 10.1242/dev.00200
|View full text |Cite
|
Sign up to set email alerts
|

A conserved role for the MEK signalling pathway in neural tissue specification and posteriorisation in the invertebrate chordate, the ascidianCiona intestinalis

Abstract: Ascidians are invertebrate chordates with a larval body plan similar to that of vertebrates. The ascidian larval CNS is divided along the anteroposterior axis into sensory vesicle, neck, visceral ganglion and tail nerve cord. The anterior part of the sensory vesicle comes from the a-line animal blastomeres, whereas the remaining CNS is largely derived from the A-line vegetal blastomeres. We have analysed the role of the Ras/MEK/ERK signalling pathway in the formation of the larval CNS in the ascidian, Ciona in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 51 publications
11
122
1
Order By: Relevance
“…The present study identified the b6.5 blastomere as a Nodal signalling source, dependent on the specific activation of the Ci-Nodal gene in this blastomere by Ci-FGF9/16/20 signalling from vegetal blastomeres. However, ERK1/2 activation is observed in both b6.5 and a6.5 blastomeres, and an FGFresponse element of the Ci-Otx gene is able to drive expression of a reporter gene in both lineages (Bertrand et al, 2003;Hudson et al, 2003). We propose that the transcriptional activation of Ci-Nodal in b6.5 but not in a6.5 is due to a difference in competence between a-and b-line blastomeres to respond to FGF-signalling, as has been previously observed during the formation of anterior neural fates and sensory neurons (Hudson and Lemaire, 2001;Ohtsuka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study identified the b6.5 blastomere as a Nodal signalling source, dependent on the specific activation of the Ci-Nodal gene in this blastomere by Ci-FGF9/16/20 signalling from vegetal blastomeres. However, ERK1/2 activation is observed in both b6.5 and a6.5 blastomeres, and an FGFresponse element of the Ci-Otx gene is able to drive expression of a reporter gene in both lineages (Bertrand et al, 2003;Hudson et al, 2003). We propose that the transcriptional activation of Ci-Nodal in b6.5 but not in a6.5 is due to a difference in competence between a-and b-line blastomeres to respond to FGF-signalling, as has been previously observed during the formation of anterior neural fates and sensory neurons (Hudson and Lemaire, 2001;Ohtsuka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The Ras/MEK/ERK/Ets signalling pathway, which is activated downstream of FGF-like signalling, has been implicated in posteriorisation of the neural tube (Akanuma and Nishida, 2003;Hudson et al, 2003). In embryos in which this signalling pathway is inhibited, markers of posterior neural fate are lost and a greater number of A-line cells express markers of the anterior CNS.…”
Section: Introductionmentioning
confidence: 99%
“…3b). Ci-Mnx is expressed in the ventral nerve cord-lineage cells in normal embryos (Hudson et al 2003; Fig. 3c).…”
Section: Alteration Of Gene Expression Pattern By Overexpression Of Cmentioning
confidence: 94%
“…FGF signaling is mediated in vertebrate embryos by the Ras/MEK/MAPK cascade. In ascidians, these intermediates have been shown to play a conserved role during formation of the secondary notochord cells, as well as in the specification of the neural tissue (Kim and Nishida, 2001;Hudson et al, 2003).…”
Section: Larval Tissues Notochordmentioning
confidence: 99%